Sistem Informasi Bimbingan Konseling Berbasis Web (Studi Kasus : SMA N 1 Jatilawang) - Nuramadanti, Izati; Wijaya, Dhina Puspasari; Yazid, Ahmad Subhan; Danianti, Dita (Jurnal Profesi Insinyur Universitas Lampung, 2025)
This study was conducted in response to the problems of counseling services at Jatilawang 1 Public High School, which were not optimally managed due to the limited number of guidance counselors, the high number of students, and the manual nature of counseling records. These conditions resulted in delays in handling cases and difficulties in continuously monitoring student progress. This study aims to design and implement a web-based counseling information system that can support the structured and integrated management of counseling services. The research method used is Research and Development with the Waterfall development model. The system is designed using Unified Modeling Language (UML) modeling and implemented using the PHP programming language with the Laravel framework and MySQL database. To support the determination of counseling service priorities, the system applies a Priority Scheduling algorithm that considers the urgency level of student problems. Testing results using the Black Box Testing method showed that the system was able to accelerate the scheduling process, improve the regularity of counseling data management, and support collaboration between guidance counselors, students, homeroom teachers, principals, and parents. Thus, this system is expected to improve the effectiveness and quality of guidance counseling services in secondary schools.